-(6y+w)-2(-2w+4y)=

Simple and best practice solution for -(6y+w)-2(-2w+4y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(6y+w)-2(-2w+4y)= equation:


Simplifying
-1(6y + w) + -2(-2w + 4y) = 0

Reorder the terms:
-1(w + 6y) + -2(-2w + 4y) = 0
(w * -1 + 6y * -1) + -2(-2w + 4y) = 0
(-1w + -6y) + -2(-2w + 4y) = 0
-1w + -6y + (-2w * -2 + 4y * -2) = 0
-1w + -6y + (4w + -8y) = 0

Reorder the terms:
-1w + 4w + -6y + -8y = 0

Combine like terms: -1w + 4w = 3w
3w + -6y + -8y = 0

Combine like terms: -6y + -8y = -14y
3w + -14y = 0

Solving
3w + -14y = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '14y' to each side of the equation.
3w + -14y + 14y = 0 + 14y

Combine like terms: -14y + 14y = 0
3w + 0 = 0 + 14y
3w = 0 + 14y
Remove the zero:
3w = 14y

Divide each side by '3'.
w = 4.666666667y

Simplifying
w = 4.666666667y

See similar equations:

| w=39 | | 0.35/3=18/c | | 4x+10=6x+15 | | x-2(x+3)=0 | | (3z+5)(7-z)=0 | | 20=-8w+5(w-2) | | 15x+3=49 | | S/3-8=23 | | 0=-16t^2+184t+20 | | 6.6x-3+x-1.7=0 | | 5x+15=4x+12 | | -2p-4=10 | | 2b+(-9)=-17 | | 2a-24=3b | | 3n-19=16 | | 4(x-9)=8(x+1) | | 7+2.50x=49.50 | | 8x+8+1= | | 35/5=81/x | | 0=-16t^2+32t+6 | | 6x+1=4x+2 | | (p^5/6x)^5 | | 2(7+n)=-10 | | 7x^2+100x-24=0 | | x+7-x=-5 | | x+20=2x+80 | | 45+90x=855 | | 5x+252=14x-9 | | 30-6x=12-8x | | 6t^2=-t+2 | | 7X+3Y+36=0 | | 12m+8-5m+2+m=6(m-1) |

Equations solver categories